Fractography and Tensile studies on the effect of different carbon fillers reinforced hybrid nanocomposites (Fracture and Structural Integrity, 2023)
The use of elastomers has become increasingly important in a variety of industries, including automotive, medical, and food packaging. The adaptability of elastomers to different mechanical stresses has made them a popular choice for these applications. However, the mechanical properties of elastomers can be further enhanced by adding suitable fillers. In this study, the effects of different carbon fillers, namely carbon black, carbon graphite, and carbon nanotubes, on the tensile strength of elastomeric materials were investigated. Different combinations of plain silicone with varying concentrations of CB, CG, and CNT fillers were prepared using a solution casting method. The concentrations of the fillers ranged from 5% to 15% with an interval of 5%. The tensile strength of each combination was measured, and the results showed that the maximum tensile strength was achieved with the combination of CNT at 15% loading. The results of this study highlight the importance of filler selection in enhancing the mechanical properties of elastomers. Carbon fillers, particularly CNTs, have shown to be effective in improving the tensile strength of elastomeric materials. This has important implications for various industries, particularly in the development of new materials for applications in the automotive and medical fields.The use of elastomers in the automotive industry has become increasingly important due to their ability to absorb mechanical shocks and vibrations. Elastomeric materials have also found applications in the medical field, such as in the development of artificial skin, blood pumps, drug delivery systems, and implants. The use of elastomers in food packaging has also become popular due to their ability to provide a barrier against oxygen and moisture.The use of carbon fillers in elastomeric materials has the potential to significantly enhance their mechanical properties, particularly their tensile strength. This study provides valuable insights into the effects of different carbon fillers on the tensile strength of elastomers, which can help in the development of new materials for various industrial applications.
Keywords: Brittle fracture; Carbon nano tube (CNT); Fracture; polymer composite material